Pengaruh Konsentrasi Jenis Asap Cair dan Konsentrasi Nira Lontar Terhadap Mutu Organoleptik Cakalang (Katsuwonus Pelamis L) Asap - Naema Bora (Jurnal Teknologi Pangan, 2022)
This study aims to determine the effect of different concentrations of liquid smoke and palm sap on the quality of smoked cakalang. The method used in this research is an experimental method which is designed completely randomized design (CRD) factorial pattern with 2 treatment factors, namely the type of liquid smoke factor and the lontar juice concentration factor. The parameters measured were organoleptic quality, which included: color, taste, aroma, moisture content, pH and total acid. From the results obtained, it can be concluded that: (1) The use of liquid smoke from kusambi wood and coconut shells significantly improves the organoleptic quality of skipjack tuna smoke during the storage period; (2) The concentration of lontar sap in liquid smoke had a significant effect on the organileptic quality of skipjack tuna during the storage period; (3) The concentration of lontar juice of 25% plus 75% of liquid smoke significantly improves the organleptic quality of skipjack tuna which includes color, taste, aroma, moisture content, pH and total acid. It is recommended to apply the use of liquid smoke raw material either from the type of kusambi wood or from the coconut shell with the addition of 25% lontar sap to improve and maintain the best smoked skipjack flavor quality.